Effects of GnRH and PGF2ï¡ Injection on Progesterone Profile of Postpartum Dairy Cow - Rasad, SD (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
A research of progesterone profile on postpartum dairy cows after GnRH and PGF2a treatment had been conducted to determine the skim milk progesterone profiles, which enhance ovarian activity in postpartum dairy cows.Â It is expected that by this treatment, the interval to first estrus could be reduced, and frequency of estrus and percentage of estrus expression could be increased. Twenty cows were randomly assigned to four treatment groups including Control group, which contain respectively 5 cows each group.Â Cow (n=5) in group I received 200 mg GnRH i.m. on days 10-14 p.p.; in group II received 15 mg PGF2a on days 20-24 i.m. p.p.; and group III received combination of both.Â The control group did not receive hormonal treatments.Â The research used multivariate, completely randomized design, univariate F-test and Duncanâs Multiple Range Test. Results showed that the postpartum interval to first estrus was shorter in treated groups (I, 26 d; II, 22 d, and III, 24 d) as compared to control group (54 d, P< 0.05).Â The percentage of estrus increased (60%) in group II and III, but no significant differences were found between group I and the control group (40%). Our result suggested that the combination treatment of GnRH and PGF2a (GnRH + PGF2Î±) enhanced activity in the postpartum cows, resulting in improved reproductive performance. (Animal Production 10(1): 16-21 (2008)Â Key Words: GnRH, PGF2a , progesterone profile, postpartum dairy cow